Realizing omnidirectional light harvesting by employing hierarchical architecture for dye sensitized solar cells. Issue 10 (22nd February 2016) - Hsieh, Ming-Yang; Lai, Fang-I; Chen, Wei-Chun; Hsieh, Min-Chi; Hu, Hsiang-Yi; Yu, Peichen; Kuo, Hao-Chung; Kuo, Shou-Yi
Abstract : To improve the omnidirectional light-harvesting in dye-sensitized solar cells (DSSCs), here we present a dandelion-like structure composed of ZnO hemispherical shells and nanorods. Abstract : To improve the omnidirectional light-harvesting in dye-sensitized solar cells (DSSCs), here we present a dandelion-like structure composed of ZnO hemispherical shells and nanorods. Uniformly distributed hemispherical shells effectively suppress the reflection over the broadband region at incident angles up to 60°, greatly improving the optical absorption of the DSSCs. In addition, modulating the length of the ZnO nanorods controls the omnidirectional characteristics of DSSCs. This phenomenon is attributed to the degree of periodicity of the ZnO dandelion-like structures. Cells with shorter rods exhibit a high degree of periodicity, thus the conversion efficiencies of the cells show specific angle-independent features. On the other hand, the cells with longer lengths reveal angle-dependent photovoltaic performance. Along with the simulation, the cells with dandelion-like ZnO structures can couple incident photons efficiently to achieve excellent broadband and omnidirectional light-harvesting performances experimentally, and the DSSCs enhanced the conversion efficiency by 48% at large incident angles. All these findings not only provide further insight into the light-trapping mechanism in these complex three-dimensional nanostructures but also offer efficient omnidirectional and broadband nanostructured photovoltaics for advanced applications.